Penentuan Laba Produk Rumahan Lemper dengan Pendekatan Full Costing - Tripalupi, Ramadhani Irma; Agustin, Dinar Aulia; Dewi, Divani Paramitha (CV. Kalimasada Group, 2023)
This research aims to calculate the cost of production based on the cost of the process using a full costing approach, and determine the profit to be obtained. The research was conducted at Lemper X Home Industry in Bandung. The type of data taken is in the form of qualitative and quantitative data, sourced from primary data and secondary data through interviews and documentation. The secondary data is in the form of library research. The results of the study show that the full costing approach can determine the cost of production based on the cost of production and the amount of profit earned. However, because there is no comparison of the results of production costs with the calculation of the variable costing approach, it is not yet known whether the information regarding the determination of profit is appropriate. No calculations were made using the variable costing approach because there were limitations in terms of variable cost data. Therefore, this research recommends that the cost of production is also calculated using the variable costing approach so that the calculation of the cost of production can be obtained which is more in accordance with the needs and can determine the appropriate profit. Thus the company will also get more accurate and precise information, in determining profits and in terms of costs where it is possible to deduct both costs of process and costs of order and in determining the appropriate approach to costs of process and costs of order. Keywords: Cost of Orders, Cost of Processing, Full Costing, Profit, Variable Costing.